Managing intercultural conflict effectively - Ting-Toomey, Stella (Communicating effectively in multicultural contexts, 2001)
This title aims to improve understanding and communication among individuals from different cultural backgrounds and explains the culture-based situational conflict model, including the relationship among conflict, ethnicity, and culture; and integrates theory and practice in the discussion of interpersonal conflict in culture, ethnic, and gender contexts.